Development of PBL-based lichens diversity e-module to improve students' problem-solving skills - Najib , Iqbal Ainun; Sari , Murni Sapta; Hastuti , Utami Sri; Balqis, Balqis (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2023)
Problem-solving skills are important things everyone needs to have to improve their quality of life. The results of a needs analysis carried out on Biology students at the State University of Malang show that their problem-solving abilities are still relatively low in lichen diversity material. This research aims to determine the development of PBL-based lichens diversity e-module and its influence on students' problem-solving skills completeness e-module and its effect on students' problem-solving skills. This type of research is a development study (development research) with the ADDIE development model. This research was conducted at the State University of Malang in biology class with a sample size of 67 students. The research instrument uses problem-solving pretest and posttest sheets, as well as material expert questionnaires, media expert questionnaires, and practicality questionnaires from educators who will use the e-module. Data were analyzed using Analysis of Covariance (ANCOVA). The results showed that the e-module developed was a very good product and could be used in learning Lichen material. The results of the study stated that the e-module was effective in improving problem-solving skills (sig. ˂ 0.05). So, it can be concluded that the PBL-based e-module is effective for improving problem-solving skills in biology students of the State University of Malang.